A Deep Dive into Deep Learning - Anuradha Desai; Disha Devani; Dr. Premal Patel (International Journal of Engineering and Management Research, 2023)
Deep learning is a technique for mimicking the human brain by intimating human functionality and attempting to uncover fruitful patterns in data using a neural network. With the increase in data volume, deep learning is becoming more popular. End devices such as smartphones and IoT sensors generate data that must be appropriately analyzed using deep learning models. This paper intends to present the reader with complete understanding of the fundamentals of deep learning elements in order to make the principles more evident in the deep learning field. This study focuses on the three major types of neural networks that serve as the foundation of deep learning models. The three primary types are as follows: i) Artificial Neural Network, ii) Convolution Neural Network and iii) Recurrent Neural Network. Let's take a deep dive into each of these sorts.